How significant was the role of Migrante, The Center for Migrant Advocacy (CMA), and the Alliance of Migrants and Advocates to Amend RA 8042 (AMEND) in the framing of the coverage of the Angelo De La Cruz abduction in Iraq? a framing analysis of news stories in the Philippine Daily Inquirer (PDI) and the Philippine Star (PhilStar) from July 9-23, 2004 - Varona, Karen Yson
"This research examines the significance of the role of Migrante, CMA and AMEND in the framing of the coverage of the Angelo de la Cruz case in PDI and Philstar from July 9-23, 2004; and how PDI and Philstar framed news stories on the case during the said period. Framing analysis and critical theory serve as framework, while document/text and content analysis, as well as interviews, serve as primary methods. The results showed that while the de la Cruz case was recurrent and prominent in PDI and Philstar coverage from July9-23, 2004, the advocacy frames of Migrante, CMA and AMEND in terms of problem definition, responsibility attribution, treatment recommendation, and language and imagery did not predominate. Moreover, Migrante, CMA and AMEND did not predominate as source proponents and were generally portrayed negatively during the case. Interview results also showed that PDI and Philstar on the one hand, and Migrante, CMA and AMEND, on the other, had a generally unfavorable perception of each other's practices during the case. Overall, the findings indicated that Migrante, CMA and AMEND did not play a significant role in PDI and Philstar framing of the de la Cruz case from July 9-23, 2004."